2018
DOI: 10.1021/acsmacrolett.8b00728
|View full text |Cite
|
Sign up to set email alerts
|

Probing Membrane Hydration at the Interface of Self-Assembled Peptide Amphiphiles Using Electron Paramagnetic Resonance

Abstract: The relative hydrophilicity at the interface of a nanoparticle was measured utilizing electron paramagnetic resonance (EPR) spectroscopy. The supramolecular structure was assembled from spin-labeled peptide amphiphiles (PA) derived from N-carboxy anhydrides (NCA). Cyanuric chloride, or 2,4,6-trichloro-1,3,5-triazine (TCT), was used as a modular platform to synthesize the spin-labeled, lipidmimetic macroinitiator used for the ring-opening polymerization of γ-benzyl-L-glutamic acid NCA to produce polyglutamate-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…2 and SI-3 †), can be used to compare the mobility among spin-labeled sites. [62][63][64][65][66][67][68] Line shape parameters such as the intensities and widths of each of the three transitions can also be utilized to determine an effective correlation time, as was shown for earlier methods where sialic acid residues were selectively modied with a nitroxide label. 69 For a nitroxide such as 3 dissolved in solvent ( Fig.…”
Section: Spin Label Mobility Varies With Glycan Type In Ls174t Cellsmentioning
confidence: 99%
“…2 and SI-3 †), can be used to compare the mobility among spin-labeled sites. [62][63][64][65][66][67][68] Line shape parameters such as the intensities and widths of each of the three transitions can also be utilized to determine an effective correlation time, as was shown for earlier methods where sialic acid residues were selectively modied with a nitroxide label. 69 For a nitroxide such as 3 dissolved in solvent ( Fig.…”
Section: Spin Label Mobility Varies With Glycan Type In Ls174t Cellsmentioning
confidence: 99%
“…One key aspect in the future of PAs is the use of molecular probes to determine local structure and properties and how this may translate into control over structure. In a recent study, Smith and co-workers produced PAs containing a poly­(glutamic acid) headgroup (with varying molecular weight,) two lipophilic tails, and a spin-label placed at the interface . They found that these PAs assembled into vesicles, and as the solution pH increased, the spin-label mobility and local polarity at the interface increased.…”
Section: Peptide Amphiphilesmentioning
confidence: 99%
“…In a recent study, Smith and co-workers produced PAs containing a poly(glutamic acid) headgroup (with varying molecular weight,) two lipophilic tails, and a spin-label placed at the interface. 55 They found that these PAs assembled into vesicles, and as the solution pH increased, the spin-label mobility and local polarity at the interface increased. This proof-of-concept study is significant because it shows the ability to probe local structure using small probes (i.e., not large fluorescent tags, so as to not disrupt morphology) using techniques common to structural biology.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 24 Other isolated coarse-grained experiments probing polymer behavior have been published, such as a 15A resolution Cryo-EM structure 25 of a PEG-bottlebrush-modified virus-like particle (a privileged system with high symmetry), and motional dynamics probed by electron paramagnetic resonance (EPR) on the surface of polymer-modified self-assembling peptide amphiphiles. 26 …”
Section: Introductionmentioning
confidence: 99%
“…24 Other isolated coarse-grained experiments probing polymer behavior have been published, such as a 15A resolution Cryo-EM structure 25 of a PEG-bottlebrush-modied virus-like particle (a privileged system with high symmetry), and motional dynamics probed by electron paramagnetic resonance (EPR) on the surface of polymer-modied selfassembling peptide amphiphiles. 26 Finally, most structural information has been on PEGconjugates, which constitute a subset of protein-polymer bioconjugates. Thus, experiments that report on conformations and proximities within protein-polymer bioconjugates are greatly needed.…”
Section: Introductionmentioning
confidence: 99%